ADULTERY IN THE DIGITAL AGE FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW - Farohah Atul Asyuro Asyuro; Utang Ranuwijaya; Fandy Adpen (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of digital technology has transformed patterns of social interaction and child-rearing practices in modern families. This situation calls for a reinterpretation of the concept of hadhanah in Islamic family law, which has traditionally focused more on the physical protection and basic education of children. This study aims to analyze the concept of hadhanah from the perspective of Islamic family law, assess its relevance to the principles of maqashid syariah, and formulate an adaptive parenting approach to address the challenges of child protection in the digital space. The study employs a qualitative method with a legal-normative approach through an examination of classical fiqh literature, the Compilation of Islamic Law, and national regulations such as the Child Protection Act, the ITE Law, and Government Regulation No. 17 of 2025 on Child Protection in the Digital Space. The findings indicate that the concept of hadhanah needs to be expanded to include aspects of digital literacy and competence as part of caregiver eligibility. The integration of fiqh values, maqashid syariah, and national regulations is essential to realizing a more adaptive, safe, and relevant parenting model for children in the digital age.